Preparation of uniform ZnO microparticles by hydrothermal methods; Conventional vs. microwave heating - Ruth, McBride (Trinity College (Dublin, Ireland). School of Chemistry, 2001)
Uniform particles of ZnO and Zn(OH)2 have been prepared in the micron size range, using a number of hydrothermal methods. In a forced hydrolysis procedure, when aqueous zinc nitrate solutions are reacted with sodium hydroxide, precipitation of either zinc oxide or zinc hydroxide can take place. At temperatures above 55 °C, ZnO star-like particles precipitate from solution and grow to a size of approximately 6.5 μm, with a distribution of 4.0 to 10.0 μm after five hours ageing at reflux temperature. Alternatively, precipitation at room temperature gives Zn(OH)2 rhombic particles. Thermal decomposition of this Zn(OH)2 in the reaction suspension, results in the formation of needle-like ZnO particles with average dimensions of 4.5 μm (L) x 1.0 μm (W) and a length distribution of 2.5 to 7.5 μm. Variations in reactant concentrations, ageing times, zinc salt counter-ion and pre-stirring times have been carried out to examine the effect of each parameter on the particles formed. The growth mechanisms for the formation of star-like ZnO, rhombic Zn(OH)2 and needle-like ZnO have been investigated using SEM, XRD and EDTA titration. It has been found that star-like ZnO grows by a diffusional growth mechanism with multiple nucleation events. The star-like morphology is believed to be a result of twinning along the (1122) plane of the hexagonal lattice. Rhombic Zn(OH)2 also grows by diffusion with multiple nucleations; however, unlike star-like ZnO, a self-sharpening step appears to takes place. Needle-like ZnO results from the thermal decomposition of Zn(OH)2, by loss of H2O from the lattice. Evidence suggests that this takes place by a solid phase transformation, without dissolution of Zn(OH)2 and subsequent re-precipitation of ZnO. The uniformity of the needle-like ZnO sample is dependent upon the uniform nature of the Zn(OH)2 particles.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin